To the blessed memory of Academician Korzh Olexiy Olexandrovych - UAOT, Staff of (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2010)
The article is dedicated to the blessed memory of Academician Korzh Olexiy Olexandrovych